Effects of Exogenous Transferrin on the Regulation of Iron Metabolism and Erythropoiesis in Iron Deficiency With or Without Anemia - Li, Yihang; Miller, Ian; Prasad, Princy; George, Nisha Ajit; Parrow, Nermi L.; Fleming, Robert E. (Frontiers in Physiology, 2022)
Erythropoietic response is controlled not only by erythropoietin but also by iron. In addition to its role in iron delivery, transferrin also functions as a signaling molecule, with effects on both iron homeostasis and erythropoiesis. We investigated hematologic parameters, iron status and expression of key proteins, including the hepatic iron regulatory protein hepcidin and the suppressive erythroid factor Erfe, in mice subject to dietary iron deficiency with and without anemia. The acute effect of iron on these parameters was investigated by administration of exogenous iron-loaded transferrin (holoTf) in each of the mouse models. Serum iron in mice with iron deficiency (ID) is modestly lower with hematologic parameters maintained by utilization of iron stores in mice with ID. As expected, erythropoietin expression and concentration, along with marrow Erfe are unaffected in ID mice. Administration of holoTf restores serum iron and Tf saturation levels to those observed in control mice and results in an increase in hepcidin compared to ID mice not treated with holoTf. The expression of the Bmp signaling molecule Bmp6 is not significantly increased following Tf treatment in ID mice. Thus, the expression level of the gene encoding hepcidin, Hamp1, is increased relative to Bmp6 expression in ID mice following treatment with holoTf, suggesting that Tf saturation may influence Bmp sensitivity. In mice with iron deficiency anemia (IDA), decreased hematologic parameters were accompanied by pronounced decreases in serum and tissue iron concentrations, and an increase in serum erythropoietin. In the absence of exogenous holoTf, the greater serum erythropoietin was not reflected by an increase in marrow Erfe expression. HoloTf administration did not acutely change serum Epo in IDA mice. Marrow Erfe expression was, however, markedly increased in IDA mice following holoTf, plausibly accounting for the lack of an increase in Hamp1 following holoTf treatment in the IDA mice. The increase in Erfe despite no change in erythropoietin suggests that Tf acts to increase erythropoietin sensitivity. These observations underscore the importance of Tf in modulating the erythropoietic response in recovery from iron deficiency anemia, with implications for other stress erythropoiesis conditions.